Navigation of the paradoxical landscape of the family business. (May 2020) - McAdam, Maura; Clinton, Eric; Dibrell, Clay
The aim of this special issue is to enhance knowledge and understanding of the distinctive, paradoxical landscape of the family business. In particular, it investigates the strategies used by family businesses to manage such tensions and to navigate this landscape where numerous paradoxes relating to family businesses have been identified. Moores and Barrett provide an overview of this distinctive, paradoxical landscape, which comprised a systematic literature review of 203 items spanning an eighteen-year period. After a rigorous reviewing process, three papers were selected for inclusion in this special issue, namely, Radu-Lefebvre and Randerson; Helvert-Beugels, Flören and Nordqvist; and Discua Cruz, which accumulatively improve our understanding of the antecedents, consequences and dynamic processes of paradoxical tensions within a family business. Finally, future research directions which acknowledge the family businesses as ageless, mindful, intuitive, collaborative and paradoxical are provided.